Effectiveness of Carbon Tax as a Legal Norm for Industrial Decarbonization: A Critical Policy Review in Indonesia - Som Chai; Napat Chai; Ton Kiat; Andi Andi (Yayasan Adra Karima Hubbi, 2025)
Background. Industrial activities are a major contributor to greenhouse gas emissions in Indonesia, posing significant challenges for environmental sustainability and climate policy. Carbon taxation has emerged globally as a legal and economic instrument to incentivize industrial decarbonization, but its effectiveness within the Indonesian regulatory and economic context remains underexplored. Purpose. Understanding the strengths, limitations, and implementation challenges of carbon tax as a legal norm is critical for designing policies that achieve emissions reduction without undermining industrial competitiveness. Method. Findings indicate that while carbon taxation has potential to drive emission reductions, challenges such as policy ambiguity, compliance enforcement, and economic impacts on industries limit its current effectiveness. Results. Findings indicate that while carbon taxation has potential to drive emission reductions, challenges such as policy ambiguity, compliance enforcement, and economic impacts on industries limit its current effectiveness. Conclusion. The study concludes that successful implementation requires a coherent legal framework, transparent regulatory mechanisms, and integration with complementary environmental policies. Strengthening institutional capacity and ensuring stakeholder engagement are essential for maximizing the efficacy of carbon tax as a tool for industrial decarbonization.